ANALISIS HUKUM PENYALAHGUNAAN NARKOTIKA UNTUK DIRI SENDIRI - Rustama Ndruru (Jurnal Panah Hukum, 2026)
Narcotics are artificial substances or derived from plants that have hallucinatory effects, decrease consciousness, and cause addiction. Narcotics crime is an act that violates the law and is an organized crime, one of the narcotics crimes examined and tried by the Bengkayang District Court, namely decision number 67/Pid.Sus/2020/PN.Bek. in this decision, the perpetrator was sentenced to only 2 (two) years in prison for violating Article 127 paragraph (1) of Law number 35 of 2009 concerning narcotics. Based on the judge`s decision against the defendant, the author is interested in conducting research with the title "legal analysis of Narcotics Abuse for Yourself". The type of research used is normative legal research with approach methods, statutory approaches, case approaches, analytical approaches. Data collection was carried out using secondary informasi, which was obtained through library materials consisting of primary, secondary and tertiary legal materials. The informasi analysis used is qualitative informasi analysis, which is descriptive in nature and drawing conclusions is carried out using bagus deductive method. Based on the research findings and discussion, it can be concluded that the imposition of sentences on perpetrators of narcotics crimes who were examined and tried by the Sleman District Court, namely (study decision number 67/Pid.Sus/2020/Pn.Bek) is not in accordance with the Law stipulated applies, where the perpetrator is sentenced to prison for only 2 (two) years, the perpetrator should be sentenced in accordance with the article that was violated by the defendant, namely Article 127 paragraph (2) of Law number 35 of 2009 concerning Narcotics, with bagus minimum prison sentence of 4 years. The author suggests that the lembaga of judges in determining sentences for narcotics criminals should be adjusted to the applicable laws and regulations.